2011
DOI: 10.1123/japa.19.3.225
|View full text |Cite
|
Sign up to set email alerts
|

Older Patient–Physician Discussion About Exercise

Abstract: This cross-sectional observational study examined the frequency of older patient–physician discussions about exercise, who initiates discussions, and the quality of questioning, informing, and support about exercise. The study used a convenience sample of 396 follow-up visits at 3 community-based practice sites, with 376 community-dwelling older patients and 43 primary-care physicians. Audiotapes were analyzed using the Multi-Dimensional Interaction Analysis coding system. Results demonstrate that exercise was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The literature regarding PA counseling practices among physicians provides a potential parallel to our findings regarding PA: receiving health-related education [23,24] and PA behavior [23,24,25,26] have been identified as important influences on whether physicians counsel their patients on PA behavior. Also similar to our findings, female physicians are more likely to counsel their patients about exercise [27,28]. In our study, gender differences in PA promotion may be attributable in part to our finding (not reported) that female clergy were more likely to report meeting PA guidelines.…”
Section: Discussionsupporting
confidence: 80%
“…The literature regarding PA counseling practices among physicians provides a potential parallel to our findings regarding PA: receiving health-related education [23,24] and PA behavior [23,24,25,26] have been identified as important influences on whether physicians counsel their patients on PA behavior. Also similar to our findings, female physicians are more likely to counsel their patients about exercise [27,28]. In our study, gender differences in PA promotion may be attributable in part to our finding (not reported) that female clergy were more likely to report meeting PA guidelines.…”
Section: Discussionsupporting
confidence: 80%
“…49 Specifically, a study with older adults found female physicians who cared for patients with a higher education (more than high school) to be significant predictors of the physicians' likelihood of providing PA counseling among older patients. 32 Very few studies reported nonphysician HCPs' counseling for PA 36,37,41,44 ; however we found that these groups, especially nurses and social workers, include regular preventive counseling recommendations more frequently than physicians into their practice.…”
Section: Physical Activity Counseling Among Hcpsmentioning
confidence: 61%
“…49 Specifically, a study with older adults found female physicians who cared for patients with a higher education (more than high school) to be significant predictors of the physicians’ likelihood of providing PA counseling among older patients. 32 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations